Carbonic anhydrase inhibitors. Phenols incorporating 2- or 3-pyridyl-ethenylcarbonyl and tertiary amine moieties strongly inhibit Saccharomyces cerevisiae β-carbonic anhydrase. (August 2014) - Bilginer, Sinan; Unluer, Elif; Gul, Halise Inci; Mete, Ebru; Isik, Semra; Vullo, Daniela; Ozensoy-Guler, Ozen; Beyaztas, Serap; Capasso, Clemente; Supuran, Claudiu T.
Abstract A series of phenols incorporating tertiary amine and trans-pyridylethenyl-carbonyl moieties were assayed as inhibitors of the β-carbonic anhydrase (CA, EC 4.2.1.1) from Saccharomyces cerevisiae, ScCA. One of these compounds was a low nanomolar ScCA inhibitor, whereas the remaining ones inhibited the enzyme with KIs in the range of 23.5–95.4 nM. The off-target human (h) isoforms hCA I and hCA II were much less inhibited by these phenols, with KIs in the range of 0.78–23.5 µM (hCA I) and 10.8–52.4 µM (hCA II). The model organism S. cerevisiae and this particular enzyme may be useful for detecting antifungals with a novel mechanism of action compared to the classical azole drugs to which significant drug resistance emerged.